Improved Path Planning of the Blade for an Automatic Spinach Harvester. Issue 2 (2020) - Takayama, Naoto; Yamaguchi, Tatsuya; Fujisawa, Akihiro; Kamijo, Tomokazu; Nakajima, Koki; Seki, Yoshifumi; Hayashi, Haruki; Chida, Yuichi
Abstract: The tendency of spinach crop to get damaged during harvesting, even when harvested by human hands, is the most significant challenge in automating the spinach harvesting process. To overcome this, an automatic spinach harvester was developed previously using a novel harvesting concept by which the crop is harvested without grasping or clamping. In this method, path planning for a root cutting blade traveling in soil is very important for successful harvesting. An effective path generation method which can handle uneven ground was proposed, but the blade motion in this method causes large variations in the depth of the path. In this study, we propose a modified path which reduces the variation in blade motion in the vertical direction by modifying the parameters of the original path generation method. Field experiments were conducted to demonstrate its effectiveness, and the results show that the modified path achieves superior harvesting performance compared to the conventional path.